Transcribing the Sacred in the Printing Era: A Study of Handwritten Buddhist Canon during the Northern Song Dynasty - Yuyu Zhang (Religions, 2023)
In an era marked by the advent of advanced printing technology during the Northern Song period, the tradition of transcribing the Buddhist canon endured rather than promptly fading away. This persistence is particularly noteworthy in the 10th to early 12th centuries when handwritten copies of the canon coexisted with the emerging prevalence of block-printed versions. Notably, the monasteries in the Jiangnan 江南 region remained prolific producers of handwritten copies. This article adopts a socio-political perspective to elucidate the coexistence of handwritten and block-printed copies. It delves into the dynamics of canon replication within a specific temporal and geographical context, unveiling a broader tableau of handwritten copies in the printing era. This exploration necessitates an examination of the intricate interplay between the state, the canon, and Jiangnan society. This study contends that the state’s printing policies before the Xining 熙寧 period (1068–1077), which rigorously regulated the production and dissemination of canonical texts, constituted a pivotal factor in sustaining the tradition of handwritten copies. Furthermore, it identifies a sustained societal demand for possessing the canon for constructing the zhuanlun zang 轉輪藏 (revolving wheel storage cabinet), which was most pronounced in the Jiangnan region. This persistent societal need fortified the enthusiasm for transcribing the canon within Jiangnan monastic communities.